Disability Studies and Biblical Literature - Moss, C. author. aut Link
XVI, 232 p.
Keywords: The primary aim of this volume is to synthesize the two fields of disability studies and biblical studies. It illustrates how academic or critical biblical scholarship has shown that many texts involving disability in the Bible is much more nuanced than a casual reading or isolated proof texting may indicate.